Management of caesarean scar ectopic pregnancy: a case report - Virmani, Smritee; Kaul, Pushpa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Caesarean scar ectopic involves an abnormal implantation of the embryo within the myometrium of previous caesarean scar. It is a rare and serious entity involving maternal complication like abnormal placentation, hemorrhage or death due to uterine rupture. Authors present a case report of 32 years old female diagnosed as a case of caesarean scar ectopic pregnancy on TVS and MRI and managed conservatively by USG guided D and C.